The effectiveness of the vote recapitulation information system Application (Sirekap) in the recapitulation of election votes in Karangwungulor Village, Laren District, Lamongan Regency - Ikhfananfalul Funuha; Meirinawati M; Eva Hany Fanida; Trenda Aktiva Oktariyanda (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The Recapitulation Information System (SIREKAP) application was developed by the General Elections Commission (KPU) to support digital vote recapitulation. This study aims to analyze the effectiveness of the SIREKAP application in vote recapitulation in Karangwungulor Village, Laren District, Lamongan Regency. The study used a qualitative approach with descriptive methods through interviews, observation, and documentation. The results indicate that SIREKAP is quite effective in accelerating the delivery of recapitulation results and increasing information transparency. However, its effectiveness is not optimal due to internet network constraints, system instability, limited human resources, and data reading errors by the OCR system. Improvements in technical aspects, human resource capacity, and supporting infrastructure are needed for SIREKAP to function optimally, especially in rural areas.